Distribution of within-ring internal checking in Pinus radiata grown in southern chile - Aguilera, A.; Inzunza, L. (Maderas. Ciencia y Tecnología, 2025)
The increase of Pinus radiata plantations in Chile has brought larger annual volumes to the industry and the opportunity to process them into value-added products. Within-ring checks constitute an impor-tant problem that may affect the appearance quality of lumber. This problem occurs in the early wood portion of sapwood growth rings in dry lumber and can only be seen when the board is cross cut. The purpose of this study was to analyze the frequency of within-ring internal checking in kiln-dried Pinus radiata lumber from different logs grown in southern Chile. Centre boards were more affected by the internal checking. Checks were located more frequently between rings 4 to 6. El incremento de las plantaciones de Pinus radiata en Chile ha entregado importantes volúmenes a la industria y por lo tanto la oportunidad de transformarlos en productos de alto valor. Las grietas internas constituyen un problema que puede afectar la calidad de la madera, en particular en aquellos productos que se clasiﬁ can por su apariencia. Este problema se puede apreciar en la zona de madera temprana de la albura en madera seca y sólo cuando la madera es trozada. El propósito de este estudio fue el de analizar, la frecuencia de aparición de grietas internas inter-anulares en madera seca de Pinus radiata. Como resultados, se encontró en las tablas centrales, com-puestas por madera juvenil, una alta frecuencia de grietas internas entre los anillos 4 y 6.